Implementación de la metodología de planificación y control “Last Planner” en el proyecto de construcción: Unidad Productiva San Rafael - Rodríguez-Porras, Katherine (Instituto Tecnológico de Costa Rica, 2017)
The main purpose of this project is to implement a planning and control system to improve the fulfillment of the activities that constitute a construction project for a period of 10 weeks. The Last Planner System (LPS) utilize Lean Construction philosophy, whose main objective is based in the obtaining of improvements of issues of great importance in the development of a work(productivity, quality, deadlines, among others) The technique consist in generate three types ofprograms, starting from a General Program, breaking it down to conform the Intermediate Program, stage that studies exposed restrictions. Finally, a Weekly Program (directly related to the person in charge of the project) that includes tasks according to the executable activities.Through meetings weekly elaborated were executed results surveys in order to quantify their behavior, evidencing the real progress through graphics, investigating the causes of noncompliance and implementing a culture of continuous improvement. The PPC (Percentage of Promises Completed) stablished a significant increase (from 43% to 63%) from the third week of study, finishing with an 83% on the tenth week. These improvements in compliance are products of a planning that is being constantly verified, taking into account the errors caused and promoting a commitment of all the staff of the project.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2017.
Keywords: Planificación; Control; Programación; Lean construction; Last planner sistem; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture